How parents share and limit their child’s access to information about COVID-19: A mixed methods online survey study - Garcia de Avila, Marla A [UNESP]; Carter, Bernie; Blake, Lucy; Saron, Holly; Kirton, Jennifer; Protheroe, Joanne; Novaes, Dayane C [UNESP]; Alencar, Rúbia A [UNESP]; Fernandes Teixeira, Tatiane R [UNESP]; Bray, Lucy (SAGE Publications, 2021)
This study aimed to understand the role that parents play in sharing or limiting their child’s access to information about coronavirus disease 2019 (COVID-19). A subset of data from an international mixed methods online survey study was analysed to elucidate the findings from Brazil. An online survey, conducted between April and June 2020, gathered closed and open text views from parents of children aged 7–12 years old. Quantitative data were analysed using descriptive statistics. Qualitative open text data were analysed using the three stages of the Bardin content analysis framework: pre-analysis (data organisation and initial full-content reading); exploration of the material (thematic coding to identify major motifs and develop thematic categories) and interpretation (treating the data as significant and valid). The sample consisted of 112 (89%) mothers and 14 (11%) fathers. The analysis of the parents open text resulted in two categories: ‘How parents share information with their children about COVID-19’ and ‘How parents limit information to their children about COVID-19’. Some parents reported adopting an honest and open approach on how they shared information with their children, whilst some parents chose to minimise their child’s access to information about the pandemic over concerns of the mortality related to COVID-19.
Keywords: Child; COVID-19; health literacy; information literacy; pandemics; parents